2021
DOI: 10.1093/jxb/erab207
|View full text |Cite
|
Sign up to set email alerts
|

In search of the still unknown function of FW2.2/CELL NUMBER REGULATOR, a major regulator of fruit size in tomato

Abstract: The FW2.2 gene is associated with the major Quantitative Trait Locus (QTL) governing fruit size in tomato, and acts by negatively controlling cell division during fruit development. FW2.2 belongs to a multigene family named the CELL NUMBER REGULATOR (CNR) family. The CNR proteins harbour the uncharacterized PLAC8 motif made of two conserved cysteine-rich domains separated by a variable region that are predicted to be transmembrane segments, and indeed FW2.2 localizes to the plasma membrane. Although FW2.2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Moreover, a recent study found that some polymorphisms in NOD alleles among maize genotypes are significantly associated with yield‐related traits in ear morphology (Zuo et al., 2021 ). Thus, NOD and NOD‐like proteins play crucial roles in agricultural species, and they could even be useful targets for plant breeders (Beauchet et al., 2021 ). Mechanistically, the Arabidopsis orthologs of NOD were first identified for their ability to complement loss of a Ca 2+ channel in yeast (and thus named MID1‐COMPLEMENTING ACTIVITY or MCA), hinting that NOD could act as a plasma membrane Ca 2+ channel (Nakagawa et al., 2007 ), although there have been conflicting reports using different methodologies to test whether NOD is capable of trafficking ions across plasma membranes in heterologous Xenopus oocyte systems (Furuichi et al., 2012 ; Rosa et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study found that some polymorphisms in NOD alleles among maize genotypes are significantly associated with yield‐related traits in ear morphology (Zuo et al., 2021 ). Thus, NOD and NOD‐like proteins play crucial roles in agricultural species, and they could even be useful targets for plant breeders (Beauchet et al., 2021 ). Mechanistically, the Arabidopsis orthologs of NOD were first identified for their ability to complement loss of a Ca 2+ channel in yeast (and thus named MID1‐COMPLEMENTING ACTIVITY or MCA), hinting that NOD could act as a plasma membrane Ca 2+ channel (Nakagawa et al., 2007 ), although there have been conflicting reports using different methodologies to test whether NOD is capable of trafficking ions across plasma membranes in heterologous Xenopus oocyte systems (Furuichi et al., 2012 ; Rosa et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that plasma membrane-associated plant FWL proteins perform diverse functions, such as cell division and organ development control, and heavy metal uptake and translocation [24,25]. However, the mechanisms underlying their distinct roles remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The FW2.2 protein harbors an uncharacterized placenta-specific 8 domain, and is localized to the plasma membrane [21,22]. FW2.2-like (FWL) genes have been characterized in various plant species and reported to perform diverse functions [23][24][25]. Cell Number Regulator1 (CNR1), an FWL gene in maize, negatively regulates plant and organ size by controlling cell division [22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes and QTLs are involved in tomato yield and individual fruit weight (reviewed in Ariizumi et al , 2013 ). For instance, Fruit Weight 2.2 (FW2.2) is a transcription factor that inhibits cell division ( Beauchet et al , 2021 ). Due to sequence variation in its promoter region, it is expressed at higher levels in wild tomatoes than in cultivated lines, causing a small fruit phenotype.…”
Section: Fruit Feedback On Fruit Growth and Retentionmentioning
confidence: 99%